1992
DOI: 10.1136/pgmj.68.806.961
|View full text |Cite
|
Sign up to set email alerts
|

Biliary tract invasion and obstruction by hepatocellular carcinoma: report of five cases

Abstract: Summary:Major biliary tract obstruction caused by tumour invasion is a rare manifestation of hepatocellular carcinoma. The authors had the opportunity to diagnose and treat five such cases, three of whom had features of acute cholangitis. The prevalence of both hepatocellular carcinoma and recurrent pyogenic cholangitis is high in patients from the Far East. The former may first present under the guise of the latter. Gastroenterologists and surgeons should be aware of hepatoceliular carcinoma when managing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…The serum total bilirubin level can rise very rapidly and correlates well with ALP and GGT levels. Similar trends could be seen in a previous report 18 . At least four patients showed negative results on either HBV or HCV tests.…”
Section: Discussionsupporting
confidence: 90%
“…The serum total bilirubin level can rise very rapidly and correlates well with ALP and GGT levels. Similar trends could be seen in a previous report 18 . At least four patients showed negative results on either HBV or HCV tests.…”
Section: Discussionsupporting
confidence: 90%
“…Since then, a few sporadic reports concerning HCC with bile duct thrombi in a small number of cases have been published. [12][13][14] Many clinicians believed that patients with icteric-type HCC had a poor prognosis compared with that of HCC patients without bile duct thrombosis. Kojiro et al 9 reported that the survival time of 24 patients with intraductal tumor growth was statistically shorter than that of controls among 238 autopsy and 21 surgical cases of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In most patients, intraductal tumor growth results from direct invasion by HCC, and obstructive jaundice progressively increases. 1 On the other hand, tumor fragments in bile ducts are usually not adherent to the duct wall and can be extracted easily, so the obstructive jaundice sometime fluctuates, possibly because of the intermittent sloughing of necrotic tumor fragments or blood clots.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Instead, jaundice is mainly caused by underlying cirrhosis and/or extensive hepatic parenchymal destruction by the tumor. Some patients with obstructive jaundice can be treated by liver resection, resulting in improved survival.…”
Section: Introductionmentioning
confidence: 97%